Risk of gestational diabetes recurrence and the development of type 2 diabetes among women with a history of gestational diabetes and risk factors: a study among 18 clinical centers in China - Wei, Yumei; Juan, Juan; Su, Rina; Song, Geng; Chen, Xu; Shan, Ruiqin; Li, Ying; Cui, Shihong; Fan, Shangrong; Feng, Ling; You, Zishan; Meng, Haixia; et al. (Chinese medical journal, 2022)
Gestational diabetes mellitus (GDM) brings health issues for both mothers and offspring, and GDM prevention is as important as GDM management. It was shown that a history of GDM was significantly associated with a higher maternal risk for GDM recurrence. The incidence of GDM recurrence was unclear because of the incidence of second-child was low before 2016 in China. We aim to investigate the prevalence of GDM recurrence and its associated high-risk factors which may be useful for the prediction of GDM recurrence in China. A retrospective study was conducted which enrolled participants who underwent regular prenatal examination and delivered twice in the same hospital of 18 research centers. All participants were enrolled from January 2018 to October 2018, where they delivered the second baby during this period. A total of 6204 women were enrolled in this study, and 1002 women with a history of GDM were analyzed further. All participants enrolled in the study had an oral glucose tolerance test (OGTT) result at 24 to 28 weeks and were diagnosed as GDM in the first pregnancy according to the OGTT value (when any one of the following values is met or exceeded to the 75-g OGTT: 0 h [fasting], ≥5.10 mmol/L; 1 h, ≥10.00 mmol/L; and 2 h, ≥8.50 mmol/L). The prevalence of GDM recurrence and development of type 2 diabetes mellitus were calculated, and its related risk factors were analyzed. In 6204 participants, there are 1002 women (1002/6204,16.15%) with a history of GDM and 5202 women (5202/6204, 83.85%) without a history of GDM. There are significant differences in age (32.43 ± 4.03 years vs. 33.00 ± 3.34 years vs. 32.19 ± 3.37 years, P  < 0.001), pregnancy interval (4.06 ± 1.44 years vs. 3.52 ± 1.43 years vs. 3.38 ± 1.35 years, P  = 0.004), prepregnancy body mass index (BMI) (27.40 ± 4.62 kg/m2vs. 23.50 ± 3.52 kg/m2vs. 22.55 ± 3.47 kg/m2, P < 0.001), history of delivered macrosomia (22.7% vs. 11.0% vs. 6.2%, P < 0.001) among the development of diabetes mellitus (DM), recurrence of GDM, and normal women. Moreover, it seems so important in the degree of abnormal glucose metabolism in the first pregnancy to the recurrence of GDM and the development of DM. There are significant differences in OGTT levels of the first pregnancy such as area under the curve of OGTT value (18.31 ± 1.90 mmol/L vs. 16.27 ± 1.93 mmol/L vs. 15.55 ± 1.92 mmol/L, P < 0.001), OGTT fasting value (5.43 ± 0.48 mmol/L vs. 5.16 ± 0.49 mmol/L vs. 5.02 ± 0.47 mmol/L, P < 0.001), OGTT 1-hour value (10.93 ± 1.34 mmol/L vs. 9.69 ± 1.53 mmol/L vs. 9.15 ± 1.58 mmol/L, P < 0.001), OGTT 2-hour value (9.30 ± 1.66 mmol/L vs. 8.01 ± 1.32 mmol/L vs. 7.79 ± 1.38 mmol/L, P < 0.001), incidence of impaired fasting glucose (IFG) (fasting plasma glucose ≥5.6 mmol/L) (31.3% vs. 14.6% vs. 8.8%, P < 0.001), and incidence of two or more abnormal OGTT values (68.8% vs. 39.7% vs. 23.9%, P < 0.001) among the three groups. Using multivariate analysis, the factors, such as age (1.07 [1.02-1.12], P = 0.006), prepregnancy BMI (1.07 [1.02, 1.12], P  = 0.003), and area under the curve of OGTT in the first pregnancy (1.14 [1.02, 1.26], P  = 0.02), have an effect on maternal GDM recurrence; the factors, such as age (1.28 [1.01-1.61], P  = 0.04), pre-pregnancy BMI (1.26 [1.04, 1.53], P = 0.02), and area under the curve of OGTT in the first pregnancy (1.65 [1.04, 2.62], P = 0.03), have an effect on maternal DM developed further. The history of GDM was significantly associated with a higher maternal risk for GDM recurrence during follow-up after the first pregnancy. The associated risk factors for GDM recurrence or development of DM include age, high pre-pregnancy BMI, history of delivered macrosomia, the OGTT level in the first pregnancy, such as the high area under the curve of OGTT, IFG, and two or more abnormal OGTT values. To prevent GDM recurrence, women with a history of GDM should do the preconception counseling before preparing next pregnancy.